KORELASI KOMPETENSI KOMUNIKASI DAN LINGKUNGAN KERJA DENGAN KINERJA APARATUR SIPIL NEGARA DI UNIVERSITAS SULAWESI BARAT - Ummi Kalsum (Universitas Terbuka, 2022)
This study aims to describe the relationship between communication competencies in aspects of communication knowledge, communication skills, and attitudes toward communicating with employee performance. The research uses a quantitative approach to collect data from the entire population consisting of all employees of the state civil apparatus at the University of West Sulawesi. The sampling was conducted proportionally stratified sampling using Slovin formula, the number of samples is 64 respondents. Research data is obtained through questionnaires, interviews, field observations, and document analysis. Data analysis is conducted through two stages, namely descriptive analysis and inferential statistical analysis using the Pearson correlation test. The results of the research obtained showed the communication competence of employees in principle has been carried out well in aspects of communication knowledge, communication skills, and communication attitudes. Correlation test results showed a positive relationship between communication competence and employee performance as evidenced by the r-count value of 0.381 > r-table 0.244. The value of coefficient determination of 0.381 means that the variance of employee performance can be explained by a competency variance of 38.1% while the rest correlates with other variables. The low significance of this variable relationship provides information that to improve employee performance it is necessary to strengthen other variables.